6th International Thematic Monograph: Modern Management Tools and Economy of Tourism Sector in Present Era 2021
DOI: 10.31410/tmt.2021-2022.35
|View full text |Cite
|
Sign up to set email alerts
|

Is the Tourism-Led Growth Hypothesis Valid for Višegrad Group Countries?

Abstract: The tourism sector represents one of the most essential segments of the world economy. This paper aims to identify the effects of tourism indicators on economic growth in terms of tourism share, international tourism arrivals and tourism employment. The subject of the paper is evaluating the impact of the tourism sector on economic growth in selected Višegrad group countries (Czechia, Hungary, Poland and Slovakia) for the period 2008-2018. The empirical findings show that the tourism sector has a significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…(2022) indicated that tourism's contribution to economic development has been scientifically verified, and this relation can be confirmed by the Tourism-Led-Growth Hypothesis (TLGH). Consequently, many theoretical and empirical researchers have analyzed the relationship between tourism and economic growth (Antonakakis et al, 2019;Arslanturk et al, 2011;Bouzahzah & El Menyari, 2013;Brida et al, 2014Brida et al, , 2020Demiröz & Ongan, 2005;Gričar et al, 2021;Gunduz & Hatemi-J, 2005; Hristov Macroeconomic Stability and Fiscal Sustainability in the Republic of Serbia Stančić et al, 2022;Kadir & Karim, 2012;Khan et al, 2020;Kim et al, 2006;Lean & Tang, 2010;Lee & Chang, 2008;Lee, 2021;Mirović et al, 2021;Perles-Ribes et al, 2017;Pratt, 2015;Shahzad et al, 2017;Sokhanvar et al, 2018;Songling et al, 2019;Tafel & Szolnoki, 2020;Wu & Wu, 2018;Wu et al, 2022). If the mentioned studies are briefly analyzed, Demiröz and Ongan (2005) investigated the impact of international tourism receipts on the long-run economic growth of Turkey from 1980 to 2004.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…(2022) indicated that tourism's contribution to economic development has been scientifically verified, and this relation can be confirmed by the Tourism-Led-Growth Hypothesis (TLGH). Consequently, many theoretical and empirical researchers have analyzed the relationship between tourism and economic growth (Antonakakis et al, 2019;Arslanturk et al, 2011;Bouzahzah & El Menyari, 2013;Brida et al, 2014Brida et al, , 2020Demiröz & Ongan, 2005;Gričar et al, 2021;Gunduz & Hatemi-J, 2005; Hristov Macroeconomic Stability and Fiscal Sustainability in the Republic of Serbia Stančić et al, 2022;Kadir & Karim, 2012;Khan et al, 2020;Kim et al, 2006;Lean & Tang, 2010;Lee & Chang, 2008;Lee, 2021;Mirović et al, 2021;Perles-Ribes et al, 2017;Pratt, 2015;Shahzad et al, 2017;Sokhanvar et al, 2018;Songling et al, 2019;Tafel & Szolnoki, 2020;Wu & Wu, 2018;Wu et al, 2022). If the mentioned studies are briefly analyzed, Demiröz and Ongan (2005) investigated the impact of international tourism receipts on the long-run economic growth of Turkey from 1980 to 2004.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Empirical findings have manifested that a 1% increase in economic growth improves tourism by 1.9% in the long term while the same increase in economic growth enhances tourism by 1.32% in the short term. Mirović et al (2021) have identified the positive impact of tourism on economic growth in Višegrad group countries (Czechia, Hungary, Poland and Slovakia) from 2008 to 2018. When it comes to European Union, Haller et al (2020) have found a positive and direct causality between tourism and economic growth in EU member states from 2012 to 2018.…”
Section: Theoretical Frameworkmentioning
confidence: 99%